2012
DOI: 10.1111/j.1365-2648.2011.05936.x
|View full text |Cite
|
Sign up to set email alerts
|

Music in mind, a randomized controlled trial of music therapy for young people with behavioural and emotional problems: study protocol

Abstract: This study will be the largest trial to date examining the effect of music therapy on young people experiencing social, emotional or behavioural difficulties and will provide empirical evidence for the use of music therapy among this population. Trial registration. This study is registered in the ISRCTN Register, ISRCTN96352204. Ethical approval was gained in October 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…Full details of this study can be found in the published protocol (Porter et al., ). After obtaining informed consent, data were collected at the participants’ home by an independent researcher.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full details of this study can be found in the published protocol (Porter et al., ). After obtaining informed consent, data were collected at the participants’ home by an independent researcher.…”
Section: Methodsmentioning
confidence: 99%
“…Reviews of the evidence suggest that MT may improve mental health in children and adolescents and communication in children with autistic spectrum disorder (Gold et al., ; Whipple, ). However, the evidence base is weak, consisting mainly of small, methodologically problematic studies (Porter et al., ). Because of the lack of unequivocal evidence, there is an urgent need for methodologically robust clinical trials to evaluate MT in diverse settings with a representative population presenting with complex and comorbid disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The RSES has been used extensively in music intervention studies (e.g. Choi, Lee, & Lee, 2010;Porter et al, 2012;Wood, Ivery, Donovan, & Lambin, 2013). It has been validated using a large sample of high school students (Rosenberg, 1965), and has since been validated for use with adults in psychiatric care and the general population (Blascovich & Tomaka, 1991).…”
Section: Meaningfulness Of Songwriting Scalementioning
confidence: 99%
“…At the same time, engagement in the creative arts has been recognised as a potentially useful instrument for improving young people's health and well-being, with some studies demonstrating the effectiveness of musical interventions for adolescents with psychopathologies (Gold et al, 2004;Gold et al, 2007Gold et al, , 2017Albornoz, 2011), and others analysing how these interventions can improve social connectedness, self-esteem and interactive skills in adolescents with behavioural difficulties as well as those suffering from bereavement (Shields, 2001;Baker & Homan, 2007;McFerran et al, 2010;Porter et al, 2012;Kim, 2015). Others have conducted research on community-based initiatives, promoting music and the arts in addressing problems facing young people, particularly those living within multiply deprived areas (Hampshire & Matjisse, 2010) and in custodial settings (Daykin et al, 2011).…”
Section: Health Well-being and Engagementmentioning
confidence: 99%